Estrategias de educación ambiental para fortalecimiento de capacidades locales de escuela Juan Bautista Aguirre, comunidad Mata de Cacao, microcuenca Carrizal - Zambrano Triviño, Ariel Gonzalo (2016)
The research aimed to evaluate the influence of methodological strategies of environmental education in strengthening local capacities of Mata de Cacao community, through the development of school gardens in the educational unit Juan Bautista Aguirre, carried out between April 2014 and April 2015 with a type of non-experimental research. Learning by doing methodology applied in the teaching-learning students in fourth, fifth and sixth grade was used; teachers and parents. The results show that children have limited knowledge of environmental education and have not received any training on the subject. The work has made the community participant group has been sensitized and created environmental awareness, the sense of responsibility shown on each activity during the development of the garden. Based on the results found a guide for teaching-learning activities for the construction of school garden as a strategy for environmental education in Mata de cacao community, contributing to strengthening local capacity was designed.